2020
DOI: 10.18203/2394-6040.ijcmph20203909
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between smartphone addiction and depression among university students in Karachi: a cross-sectional study

Abstract: Background: Pakistan demographic and health survey (PDHS) estimated extensive ownership of cell phones in Pakistan with 94.7% in the urban population. Pakistan Advertiser Company reported 77 % of cell phone users aged between 21-30 years. Although, no research was conducted with university population for addiction and depression, so this study aims to find the link between Smartphone addiction and depression in SZABIST University students of Karachi, Pakistan.Methods: Cross-sectional study was conducted with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
3
3
1
Order By: Relevance
“…Our data are consistent with ndings from other areas of research that the accumulation of risk factors, rather than the role of speci c factors, contributes to morbidity in several areas [20,36]. In previous studies, many scholars have identi ed mobile phone addiction as a signi cant risk factor for depression among university students [13][14][15]. We therefore sought to identify the predictive value of individual, family and social risk measures for depressive symptoms in university students in addition to PSU.…”
Section: The Relationship Between Components Of Risk and Depressive S...supporting
confidence: 91%
See 2 more Smart Citations
“…Our data are consistent with ndings from other areas of research that the accumulation of risk factors, rather than the role of speci c factors, contributes to morbidity in several areas [20,36]. In previous studies, many scholars have identi ed mobile phone addiction as a signi cant risk factor for depression among university students [13][14][15]. We therefore sought to identify the predictive value of individual, family and social risk measures for depressive symptoms in university students in addition to PSU.…”
Section: The Relationship Between Components Of Risk and Depressive S...supporting
confidence: 91%
“…The summing scores of depression was categorized into the 5 severity levels, i.e. normal (0-9), mild (10)(11)(12)(13), moderate (14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+) [28]. The instrument is frequently used for assessing medical students [29] and Cronbach's alpha of the Chinese version is 0.83 for the depression subscale [30].…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar trend also observed in South Korea as anxiety and depression was seen more in people who overused smartphones (Hwang et al 2012). A study in Pakistan reported that there is a correlation between smartphone addiction & depression (Abid et al 2020). Association of depression and problematic mobile usage were noticed in a young population group in Austria (Augner & Hacker 2011).…”
Section: Introductionsupporting
confidence: 61%
“…To do so, researchers employed the five symptoms of the smartphone addiction scale: disregard for negative consequences, preoccupation, inability to regulate, loss of productivity, and emotions of dread and loss. In another study, Abid et al (2020) found that there is a remarkable influence of psychological control on mobile phone dependency, self-regulated learning, and school adjustment. However, mobile phone dependency plays a vital role as a mediator in this regard.…”
Section: Literature Reviewmentioning
confidence: 97%